Overview of fruit flies important for fruit production on the Montenegro seacoast - Radonjić, Sanja; Hrnčić, Snježana; Perović, Tatjana (Biotechnologie, agronomie, société et environnement, 2019)
Description of the subject. Fruit flies are a large group of pests belonging to the order Diptera. The family Tephritidae is one of two fly families referred to as "fruit flies". Tephritidae (true fruit flies) represent one of the largest families of flies and are part of a group of the most destructive agricultural pests in the world, attacking a wide range of fruits and fleshy vegetables. The other fruit fly family is the Drosophilidae, often called "vinegar flies". There are also fly species from other Diptera families that attack the fruits of agricultural crops. Objectives. Due to its favorable geographic position and Mediterranean climate, the Montenegro seacoast is suited to fruit and vegetable production. The aim of this study was to make an inventory of the fruit fly species affecting fruit crops on the Montenegro seacoast. Method. The study area was 300 km along the Montenegro coast. Different types of traps (lure attractants, pheromone, and yellow sticky traps) were used for the monitoring, detection and recording of the spread of fruit flies in the area. Results. From an economic point of view, the most important species of fruit flies recorded were the Bactrocera oleae Gmel. and Ceratitis capitata Wiedem. Rhagoletis cerasi L. and Carpomya vesuviana Costa were also found to be present. Although several specimens of Rhagoletis cingulata Loew were detected in 2013-2014, this species has not, to date, been considered as established in the area of study. After the first detection of Drosophila suzukii Matsumura in 2013, this fruit fly was found to spread rapidly, and its presence is now observed along the whole Montenegro seacoast. One of the fruit fly species recorded, Silba adipata McAlpine, is considered to be one of the most destructive pests for fig production in Montenegro. Conclusions. Of seven species recorded in the study, five belonged to the family Tephritidae, and one each to Drosophilidae and Lonchaeidae.